THE INFLUENCE OF THE TRAINING PROCESS ON INCREASING FUNCTIONAL CAPABILITIES OF PLAYERS - V.I. Karpov; I.S. Rud (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the questions of physical loading ofplayers in football hall. The components of loading and their impact on functional abilities of students are studied.